Effect of TheraCal PT and Biodentine on inflammatory cell infiltration and hard tissue formation after pulpotomy in inflamed or healthy rat molars - Gok, Tuba; Cankaya, Guzide; Eroksuz, Yesari; Incili, Canan Akdeniz; Saygili, Suna Karadeniz (Springer Heidelberg, 2025)
Objectives TheraCal PT is a novel resin-modified calcium-silicate material introduced for vital pulp therapies. This study aimed to investigate the inflammation and hard tissue formation after pulpotomy treatment with Biodentine and TheraCal PT in inflamed or healthy rat molar teeth. Methods This study consisted of six groups (n = 12, 72 teeth): negative control-no preparation (NC); positive control (PC); Biodentine-pulpitis teeth (BD-P), TheraCal PT-pulpitis teeth (TPT-P), Biodentine-healthy teeth (BD-H), TheraCal PT-healthy teeth (TPT-P). For PC, BD-P and TPT-P groups, teeth were induced with lipopolysaccharide for 12 h. Pulpotomy procedure was performed with Biodentine and TheraCal PT. Eight weeks later, pulpal inflammatory cell infiltration and hard tissue formation were evaluated by histological analysis. Pearson's chi-square test was performed. Results There were significant differences among groups for inflammation and hard tissue formation (p <.05). PC group showed moderate to severe inflammation. Biodentine groups showed lower inflammation scores than TheraCal PT groups. Pulpitis-induced groups showed higher inflammation scores than healthy groups. In Biodentine groups, complete hard tissue formation was higher than incomplete hard tissue formation. TheraCal PT groups showed mostly incomplete or no hard tissue formation. Pulpitis-induced groups showed inferior hard tissue formation scores than healthy groups. Conclusions TheraCal PT as a pulp capping material and inflamed pulp as a pre-treatment tooth condition showed inferior results in pulpotomy treatment. Biodentine exhibited favorable inflammatory pulpal responses and thicker hard tissue formation than TheraCal PT.
Keywords: Hard tissue formation; Inflammatory cell infiltration; Rat pulpitis model; Resin-modified calcium silicate cement; Vital pulp therapy